The relationship between the 4ps marketing mix of Melaka duck tour towards domestic tourist satisfaction / Nur Aini Mohamed Nasir, Siti Naquyah Ramli and Wan Nur Asyikin Wan Azmi - Mohamed Nasir, Nur Aini; Ramli, Siti Naquyah; Wan Azmi, Wan Nur Asyikin (2015)
Customer satisfaction is one of the most important aspect in delivery the services towards the customers. The study focuses on the most attributes marketing mix towards the tourist's satisfactions. This aim of this study is to determine the most attributes marketing mix and the customer satisfactions towards the Melaka Duck Tours products and services. This study has two research questions to be answered. Furthermore, to analyze the data, the researcher used the SPSS software version 21. In additions, according to the results, the most attributes ofmarketing mix is product (0.950), followed by place (0.939), price (0.930) and promotion (0.905). The researcher has distributed 200 sets of questionnaires, but only 195 sets are returned and only 190 questionnaires are completely answered. The researcher also includes recommendations for future research, which can be very beneficial to Melaka Duck Tours.